Muslim Identity Construction in Nadine Jolie Courtney’s All-American Muslim Girl - Fahira, Dhea Faridatul; Oktafiyani, Elve (Muslim English Literature, 2025)
This research examines the construction of Muslim identity in the main character of Nadine Jolie Courtney’s All-American Muslim Girl. This research used a qualitative textual analysis with a content analysis approach, focusing on how identity is represented through the character’s dialogue, actions, and internal thoughts. Data were collected by systematically coding narrative units in the novel that reveal aspects of Allie’s identity formation. The theory of character and characterization from DiYanni is used to analyze Allie’s character, while James Marcia’s four identity status framework is used to interpret the stages of identity construction. The findings reveal that Allie develops a passive American Muslim identity, shaped by her gradual learning of Islam and practice of religious rituals. Her identity’s construction follows Marcia’s stages: (1) identity diffusion, where Allie hides her Muslim identity while benefiting from her white appearance; (2) foreclosure, where she avoids Islamic practices due to family judgement; (3) moratorium, marked by exploration and confusion in her spiritual journey; and (4) identity achievement, where she embraces her muslim identity, commits to continue learning, and chooses to stand up for Muslim rather than conceal her faith.